Analisis Kinerja Pelayanan Angkutan Perintis di Wilayah Kecamatan Liukang Tangaya Kabupaten Pangkajene dan Kepulauan - Latumahina, Glen Jimmy; Idrus, Misliah; Chairunnisa, Andi (Jurnal Penelitian Enjiniring, 2020)
Analyze Service Performance of Pioneer Transportation in Liukang Tangaya Sub-district Area, Pangkajene and Islands District. The aim of this study was to find out efficiency of the pioneer transportation performance in Liukang Tangaya Sub-district Area and the variables that affect to it, and to formulate the development strategies in the future also.The approach of this study was quantitative. Data collection performed by direct observation. Total load data processed to obtain load factor as benchmark to determine efficiency and continued by analyzing the influence variables to formulate the development strategies by using SWOT analysis. The result showed that the pioneer transportation route R-44 was efficient, where passenger load factor for line Liukang Tangaya – Maccini Baji more than 100% and cargo below 6%, with realized frequency also as much 89%. The affecting variables are the amount of cargo quantity and the amenities of load space. The development strategies that suggested are: (i) Increase the quality of passenger’s service on board as well as when in harbor, (ii) Intensify socialization related to schedule information departure of the ship either by print media or by government web sites to stimulate more cargo quantity, (iii) fleet regenerate with more greater passenger’s capacity and load space equipped with cooler, (iv) increase shipping frequency numbers so that passenger buildup would never happen.